Interprofessional Collaboration and Burnout Nurses in Hospital - Rosiana Nur Imallah; Yuni Kurniasih (Universitas Muhammadiyah Semarang, 2021)
The demand safe for nursing sarvices, effective nursing services, excellent service, high standard of clinical services, causes nurses to be in a state of prolonged stress. The prolonged stress experienced by nurses will result in burnout which will directly impact the quality of care and quality of nursing services performed. if this is allowed to continue it will have an impact on the future of the hospital. This study aimed to know the relationship between interprofessional collaboration with the incidence of burnout in the hospital. This study used a correlational design with a cross-sectional approach to time. The population in this study were nurses in IGD, ICU, and ICCU. Interprofessional collaboration had no relationship with nurse burnout (p> 0.05). The results of the analysis showed that nurses experienced burnout because it was influenced by other factors such as work environment, workload and work stress. Further analysis from the researcher shows that good interprofessional collaboration is needed in improving the performance of nurses but it is not the only factor that can affect nurses experiencing burnout.